2022
DOI: 10.1097/ju.0000000000002345
|View full text |Cite
|
Sign up to set email alerts
|

Malignancy Yield of Testis Pathology in Older Boys and Adolescents with Cryptorchidism

Abstract: Purpose:We performed a retrospective, single-institution study to characterize the pathological findings of testis tissue specimens from older boys and adolescents with cryptorchidism.Materials and Methods:With institutional review board approval, pathology reports were obtained for testicular specimens from patients age 10 years or older at a pediatric hospital from 1994 to 2016. Reports were excluded if they lacked clinical records, lacked testicular parenchyma, were from a descended testis or were from a pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Both patients had intraabdominal UDT and underwent unilateral orchiectomy in which the histopathological finding revealed seminomas. 19 The most recent report in January 2023 was published by Faruk et al, in which the authors found a right testicular seminoma in a 24-year-old man with uncorrected bilateral UDT. In the study, the patient underwent right orchiectomy and left orchidopexy followed by close monitoring every four months for the first year, every six months for the second year and then annually for the third to fifth years.…”
Section: Discussionmentioning
confidence: 99%
“…Both patients had intraabdominal UDT and underwent unilateral orchiectomy in which the histopathological finding revealed seminomas. 19 The most recent report in January 2023 was published by Faruk et al, in which the authors found a right testicular seminoma in a 24-year-old man with uncorrected bilateral UDT. In the study, the patient underwent right orchiectomy and left orchidopexy followed by close monitoring every four months for the first year, every six months for the second year and then annually for the third to fifth years.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggest that according to the relevant clinical data and the rate of testicular growth, surgery should be performed in children with cryptorchidism before the age of 1 year. Xu et al ( 52 ) analyzed the pathological reports of testicular specimens of boys with cryptorchidism aged 10 or above at a pediatric hospital from 1994 to 2016. The results showed malignant changes in 12.5% of boys with IAT but not in boys with extra-abdominal testis.…”
Section: Treatment Of Cryptorchidismmentioning
confidence: 99%
“…Xu et al (page 694) from Boston, Massachusetts look at this question in a single-institution retrospective review of pathology reports. 1 Excluding patients with differences of sexual development, they compared the malignancy rates and types between intra-abdominal testicles and all other undescended testicles. With a median age of intervention of 15 years, 12.5% of the intra-abdominal testicles had a malignancy, whereas none of the other undescended testicles had a malignancy.…”
Section: Malignancy Yield Of Testis Pathology In Older Boys and Adole...mentioning
confidence: 99%